How do law students really learn in identifying legal issues? - Abdullah, Nor Anita (2015)
Legal education depends on the active involvement of the students in the learning process.To study law is part of a process to become a professional lawyer.Being a law student is a preparation towards becoming a lawyer.The learning process is an earlier stage of getting knowledge as preparation to become as successful lawyer in the future.This is skill to be learned during the learning process from the very beginning of their life as law students in the study until their graduation then becoming a lawyer as a profession. Therefore, the students are presumed to know how to identify legal issues, to interpret the law, to solve the legal problems an$ know how to settle any legal problems arise.Thus, this article intends to identify problems jamong law students in identifying legal issues and how to overcome the problems.Action research approach was applied in this research and the respondents were selected among the law students specifically in their first semester of study.As a result, the process of collecting data also the perspective of the researcher and students.